Adding insult to injury: The fiscal impact of a failed FEMA disaster reimbursement system upon Florida municipalities - Mitchell, PhD, David; Knox, PhD, Claire Connolly (Journal of Emergency Management, 2021)
The financial aspects of natural disasters test fiscal solvency by draining municipal reserves and diverting funds from vital operations until Federal Emergency Management Agency (FEMA) reimbursements arrive, if they arrive. With record-breaking natural disasters, the resulting fiscal strain is hampering nearly every community’s effort to increase resiliency. Without systemically assessing the financial responses to natural disasters at the local government level, we are perpetuating the paradox of government disaster policy making and decreasing our community’s resiliency. This study bridges the gap between the financial management and disaster recovery literatures by applying resource dependency theory to an exploratory case study of local emergency managers and city managers in Central Florida following hurricanes Matthew, Irma, and Michael. Collectively, the respondents describe the reactive and dependent nature of the current federalist approach to natural disaster financial management practices; which ultimately threatens fiscal viability for many American communities.